RETROSPECTIVE OF STRUCTUREGENETICAL AND GEOTERMOCHRONOMETRICAL MONITORING OF METAMORPHISM AND TECTONIC EVENTS IN PREACAMBRIAN (AN EXAMPLE OF THE WESTERN REGION OF THE UKRAINIAN SHIELD) - PAVLOVA, O.; PONOMARENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
In article view an occasion of application and componentry of monitoring of the main stages of metamorphism and tectonic events in Preacambrian on an example of the western region of the Ukrainian shield. Complex application structuregenetic, mineralogy and isotopic Complex use of structure genetic, mineralogical and isotope geotermochronometric researches has allowed to fulfil a revealing of stagest and age intervals of process of termodynamic transformations of mineral associations of crystal rocks.